2009
DOI: 10.1007/s00425-009-0962-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased DNA repair in Arabidopsis plants overexpressing CPD photolyase

Abstract: Ultraviolet-B (UV-B, 280-320 nm) radiation may have severe negative effects on plants including damage to their genetic information. UV protection and DNA-repair mechanisms have evolved to either avoid or repair such damage. Since autotrophic plants are dependent on sunlight for their energy supply, an increase in the amount of UV-B reaching the earth's surface may affect the integrity of their genetic information if DNA damage is not repaired efficiently and rapidly. Here we show that overexpression of cyclob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 51 publications
(63 reference statements)
1
35
0
Order By: Relevance
“…To avoid the deleterious effects of UVR, plants have acquired two main protective strategies; shielding by flavonoids and phenolic compounds [168, 169] and DNA repair by photoreactivation. Photoreactivation mediated by the enzyme photolyases is thought to be the major DNA repair pathway in several higher plants such as rice, Arabidopsis , wheat, and maize [170172]. Studies on Arabidopsis seedling, rice, and alfalfa indicate that photoreactivation greatly enhances the rate of removal of dimers, although, in the absence of photoreactivating (blue) light, dimers are slowly eliminated from bulk DNA and 6-4PPs are generally observed to be repaired more quickly than CPDs [173, 174].…”
Section: Photoreactivationmentioning
confidence: 99%
“…To avoid the deleterious effects of UVR, plants have acquired two main protective strategies; shielding by flavonoids and phenolic compounds [168, 169] and DNA repair by photoreactivation. Photoreactivation mediated by the enzyme photolyases is thought to be the major DNA repair pathway in several higher plants such as rice, Arabidopsis , wheat, and maize [170172]. Studies on Arabidopsis seedling, rice, and alfalfa indicate that photoreactivation greatly enhances the rate of removal of dimers, although, in the absence of photoreactivating (blue) light, dimers are slowly eliminated from bulk DNA and 6-4PPs are generally observed to be repaired more quickly than CPDs [173, 174].…”
Section: Photoreactivationmentioning
confidence: 99%
“…In this study, we functionally characterized M. robertsii CPD and (6–4)PP photolyases and found that the (6–4)PP photolyase effectively removed the (6-4)PPs lesions introduced by sunlight, whereas CPDs accumulated causing cytotoxic effects and loss of virulence. As expressing a plant photolyase reduced mutations in the UV-exposed skin of mice [18], and overexpressing a native photolyase moderately increased growth of UV-treated Arabidopsis thaliana [21], we decided to investigate the extent to which photolyases could be used to engineer UV-tolerance in entomopathogens. We found that overexpressing the native M. robertsii photolyase or expressing the photolyase of a highly UV tolerant Halobacterium [22], both imparted increased UV tolerance, but the Halobacterium enzyme was much more effective and achieved a 32-fold improvement in survivability to sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…UV-hyper-resistant plants have in fact already been produced by over-expression of CPD photolyase in rice (22,72) and in Arabidopsis (29) and by that of DDB1A in Arabidopsis (2). these suggest that DnA repair mechanism is the main target of engineering plants for increased UV-resistance.…”
Section: Development Of Uv-hyper-resistant Plantsmentioning
confidence: 99%